A superfusion apparatus for ex vivo human eye irritation investigations. Issue 7 (October 2015) - Elbadawy, Hossein Mostafa; Salvalaio, Gianni; Parekh, Mohit; Ruzza, Alessandro; Baruzzo, Mattia; Cagini, Carlo; Ponzin, Diego; Ferrari, Stefano
Graphical abstract